Defense for basketball field shots - Okubo, H.; Hubbard, M. (Procedia Engineering, 2012)
A three dimensional dynamic model is used to calculate basketball motions for field shots with release conditions: release position, release velocity, backspin angular velocity, release angle, and lateral deviation angle. The model includes basketball stiffness and damping and calculates the slipping and non-slipping, and spinning and non spinning motions at the ball-contact point. The simulations, together with probabilistic selection of release conditions, analyze ball trajectories of field shots and possible rebounding positions for players. The results instruct the best rebounding position for placement of rebounders. We also investigate the effectiveness of denying the optimal shot paths for attempted blocked shots.